Introgression of common wheat lines with genetic material of Agropyron glaucum - R. O. Davoyan; I. V. Bebyakina; E. R. Davoyan; A. N. Zinchenco; Y. S. Zubanova; D. S. Mikov (Вавиловский журнал генетики и селекции)
Grey wheatgrass Agropyron glaucum (Desf. ex DC) Roem. & Schult is a valuable source of genes for resistance to diseases, frost resistance, and salt tolerance. An unstable 76-chromosomal amphidiploid combining genomes A and B of common wheat variety Avrora, six chromosomes of genome D of the same variety, and a full set of Ag. glaucum (2n = 42) chromosomes was used as an intermediate to transfer the genetic material from the wild donor to the said wheat variety. A large set of wheat introgression lines differing in a variety of morphobiological characters was developed. For effective employment of the developed lines in breeding, cytological and molecular-genetical analyses of the lines were conducted, and their pest resistance and grain technological properties were evaluated. We report the investigation of 25 common wheat introgression lines with genetic material from Ag. glaucum, not studied hitherto. All lines but D43 formed 21 bivalents in МI meiosis. In lines D3, D21, and D23, the genetic material of Ag. glaucum was present as a translocation segment. Lines D7, D43, and D49 carried substituted chromosomes and, presumably, translocations. One pair of wheat chromosomes was substituted in 18 lines. For the identification of translocations and substituted chromosomes, microsatellite analysis was done with markers specific to D genome chromosomes. The introgression touched all D genome chromosomes except 3D and 4D. The lines under the study differed in protein and gluten contents, gluten quality, and bread-making quality. Study of gliadin spectra revealed changes in the gliadin formula in 7 of 12 lines with reference to the recipient Avrora variety. Thus, the results obtained point to genetic diversity of investigated introgression lines and their value for common wheat breeding.